ANALISA PERANCANGAN SISTEM PERENCANAAN PENGENDALIAN PRODUKSI DAN PENGAWASAN BAHAN BAKU (PPIC) - Firman Ardiansyah Ekoanindiyo; Antono Adhi (Jurnal Ilmiah Dinamika Teknik, 2010)
In line with growth of era requirement of speed and of accuracy information accuracy represent vital matter in information era these days. Influence of information system to world start from educational, manufacturing, commerce until service area have earned to be felt its benefit. To execute the activity of planning require to be a natty and matured, organized, to be instructed, to be coordinated is and also observed by its execution so that can reach result of maximal. With existence of a scheme of system at company expected can add economic value at company and also can cost effective and time so that can improve work productivity and advantage at company.   Keyword: Information, Planning, Design System, Productivity